Temperature changes in the excitonic absorption band in flat double nanoheterostructures GaAs/AlxGa₁₋xAs - Kondryuk, D.V.; Derevyanchuk, A.V.; Kramar, V.M.; Kudryavtsev, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Adduced in this paper are the method and results of theoretical studying the effects of spatial confinement and exciton-phonon interaction on the position and shape of the excitonic absorption band in flat double nanoheterostructures GaAs/AlxGa₁₋xAs. The heterojunction has been considered as unstrained, the nanosystem is modeled as a rectangular quantum well of a finite depth. Interaction of exciton with optical polarization phonons has been taken into account. Calculated has been the temperature dependence of the energy corresponding to transition into the background excitonic state, and determined have been temperature changes in the absorption coefficient related with this transition. It has been shown that observation of these temperature changes in the energy and absorption coefficient, caused by interaction with optical phonons, is possible in the case of exciton with heavy hole at temperatures above 100 K.